Sistem Pembagian Waris Patrilinealpada Masyarakat Adat Lampung dalam Perspektif Maslahah - Amar Ma’ruf (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This article is the result of research on the various customs of the Lampung people, where Indonesia is a pluralistic society that adheres to various ethnic groups, religions and beliefs, and comes from diverse indigenous peoples. These differences are shown in human daily activities in their social interactions in society. , from the human being is born until he dies. Customary law is born from a behavior that is continuously carried out in which there is a certain pattern that its existence is maintained so that it becomes a habit and is recognized by the community groups in it as a tradition called adat. Likewise, the Lampung Community, which is also one of the indigenous peoples in Indonesia, which is plural in nature with a variety of language dialects, customs, and diverse lifestyles. This diversity then gave birth to a diverse culture as well. More specifically, this article discusses how the distribution of patrilineal inheritance in the Lampung Indigenous community when viewed from the perspective of Maslahah. If the distribution of traditional inheritance in Lampung is applied standardly, then the inheritance rights completely fall to the eldest son by overriding the rights of the daughter to get her inheritance rights. Meanwhile, Islam highly upholds women's rights, including in terms of inheritance distribution. To answer the problems that arise related to this, this study uses a qualitative descriptive method. then this is not in accordance with the principle of benefit, so that it does not reflect a balanced sense of justice as the Word of Allah SWT which is explained in the Qur'an about several provisions of inheritance law for the benefit of mankind, both men and women.